Kinerja Micro Grid Menggunakan Photovoltaic-Baterai dengan Sistem Off-Grid - Adhi Kusmantoro; Ardyono Priyadi; Vita Lystianingrum Budiharto Putri; Mauridhi Hery Purnomo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Renewable energy based micro grid planning is perfect for delivering electricity to rural areas, as an uninterruptible resource. In this paper, a DC micro grid system is designed. The system consists of several PVs and batteries which are connected to each other through a network. PV grids A and C deliver 1,904 watts of power in the micro grid system, while the battery contributes 784 watts of power. The system has a load of 730 watts. The purpose of this study is to improve the performance of micro grid with off-grid systems. The performance of the designed system is quite good because there sources of the grid A and grid C systems are sufficient to meet load demands and to charge batteries. When solar radiation is low, the battery meets load demands. To make the system more reliable, although it will increase system costs, a battery with a larger capacity can be used. The proposed system maintains the voltage at 12V with a change of only ± 10%.